Heartstopper. Alice Oseman. - Oseman, Alice (Hodder Children's Books, 2019)
Nick and Charlie are best friends. Nick knows Charlie's gay, and Charlie is sure that Nick isn't. But love works in surprising ways, and Nick is discovering all kinds of things about his friends, his family - and himself. 'Heartstopper' is about friendship, loyalty, and mental illness. It encompasses all the small stories of Nick and Charlie's lives that together make up something larger, which speaks to all of us.